2013
DOI: 10.1080/07900627.2012.739539
|View full text |Cite
|
Sign up to set email alerts
|

Resettlement and development: a survey of two of Indonesia's Koto Panjang resettlement villages

Abstract: Construction of the Koto Panjang Dam was initiated in response to the rapidly increasing demand for electricity in the central region of Sumatra, Indonesia. The process of resettling the villages affected by this construction lasted from 1991 to 2000. The economic factors related to this resettlement programme include monetary compensation, productive capacity, and appropriate distribution of income. Better-off villages (such as those where a rubber plantation was found) received a higher level of compensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
4
6
0
Order By: Relevance
“…The average household income per month in the two villages is 1.5 million rupiah. This fact is similar to the results of previous studies, where the condition of household/village income in West Sumatra, in general, was relatively lower than household income in villages in Riau province (Karimi and Taifur, 2013).…”
Section: B the Materials And Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The average household income per month in the two villages is 1.5 million rupiah. This fact is similar to the results of previous studies, where the condition of household/village income in West Sumatra, in general, was relatively lower than household income in villages in Riau province (Karimi and Taifur, 2013).…”
Section: B the Materials And Methodssupporting
confidence: 91%
“…This statement is evidenced by 76 percent of respondents answering that their welfare increased or better than before they moved. This condition is in line with the research of Karimi and Taifur (2013) who found the fact that 70 percent of household respondents stated that their welfare was better than before. This also indicates that the risk of impoverishment that occurs relatively successfully is overcome or minimized, thus creating a better or more prosperous society.…”
Section: Qualitative Analysis Of Household Welfaresupporting
confidence: 91%
See 1 more Smart Citation
“…The indirect impacts of compulsory land acquisition also may be substantial [11,10]. In some cases, food insecurity is a serious problem arising from compulsory land acquisition [4,13,14]. Social injustice arising from land acquisition is primarily related to inconsistencies in compensation policies in both horizontal and vertical dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…They have succeeded significantly in raising incomes. They do not need to use the reservoir but dug their fish culture ponds (Karimi and Taifur 2013).…”
Section: Discussionmentioning
confidence: 99%